2015
DOI: 10.1128/jb.02626-14
|View full text |Cite
|
Sign up to set email alerts
|

The Sinorhizobium meliloti SyrM Regulon: Effects on Global Gene Expression Are Mediated by syrA and nodD3

Abstract: In Sinorhizobium meliloti, three NodD transcriptional regulators activate bacterial nodulation (nod) gene expression. NodD1 and NodD2 require plant compounds to activate nod genes. The NodD3 protein does not require exogenous compounds to activate nod gene expression; instead, another transcriptional regulator, SyrM, activates nodD3 expression. In addition, NodD3 can activate syrM expression. SyrM also activates expression of another gene, syrA, which when overexpressed causes a dramatic increase in exopolysac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 135 publications
(186 reference statements)
0
51
2
2
Order By: Relevance
“…Previous transcriptome studies identified numerous genes that appeared to be transcriptionally regulated by ExoS/ChvI (Yao et al, ; Chen et al, ; Wells et al, ; Barnett and Long, ). However, of the ChvI‐regulated genes identified in those previous studies, only ropB1 , SMb21440 and the SMc01580 ‐ SMc01581 operon (Chen et al, ) and the SMb21188 ‐ msbA2 operon (Bélanger and Charles, ) were shown to be directly regulated by ChvI, using EMSA to detect binding between purified ChvI protein and the upstream regions of these genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous transcriptome studies identified numerous genes that appeared to be transcriptionally regulated by ExoS/ChvI (Yao et al, ; Chen et al, ; Wells et al, ; Barnett and Long, ). However, of the ChvI‐regulated genes identified in those previous studies, only ropB1 , SMb21440 and the SMc01580 ‐ SMc01581 operon (Chen et al, ) and the SMb21188 ‐ msbA2 operon (Bélanger and Charles, ) were shown to be directly regulated by ChvI, using EMSA to detect binding between purified ChvI protein and the upstream regions of these genes.…”
Section: Resultsmentioning
confidence: 99%
“…Notable ChvI direct targets identified in this study include chvI itself (Group 2), the exoY and exoH operons encoding enzymes involved in succinoglycan synthesis (Group 1), and rem , encoding a key regulator that activates expression of the class II flagellar assembly and motility genes (Group 1) (Rotter et al, ). While ChvI had been proposed to play a role in coordinating EPS‐I production and motility, evidence that motility/chemotaxis genes were directly regulated by ChvI was lacking until now (Yao et al, ; Wells et al, ; Chen et al, ; Barnett and Long, ; Barnett and Long, ). The effect of ChvI on rem transcription is negative, rather than positive as on the exo genes, and further work is needed to understand the mechanism by which ChvI down‐regulates promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…Part of the genes whose expression was activated by NodD1 and genistein lacked the promoter sequences recognized by NodD1 or TtsI (NB and TB, respectively), suggesting that other transcriptional regulators could be involved in the regulation of their expression. One of the obvious candidates was SyrM, since its orthologues participate in the nod regulon in S. meliloti and S. fredii NGR234 (Kobayashi et al, 2004;Barnett and Long, 2015). The expression of syrM is induced by NodD1 and genistein through NB19, and well conserved SyrM boxes were found upstream of two operons (psfHH103d_322-psfHH103d_319 and psfHH103d_306-psfHH103d_311) that were highly induced by genistein and lacked functional NB or TB (Pérez-Montaño et al, 2016).…”
Section: Sinorhizobium Fredii Hh103 Harbours a Single Copy Of Syrmmentioning
confidence: 99%
“…Thereby, the plant-released polyphenols and the betaines are highly specific signals that are perceived by the bacterial NodD or SyrM receptor and activator proteins, which in turn activate transcription of many symbiosis related genes (Hartwig et al, 1990; Swanson et al, 1993; Barnett and Long, 2015). The nod and nol genes encode for the strain-specific biosynthesis of chito-lipo-oligosaccharides, commonly called Nod factors.…”
Section: Discussionmentioning
confidence: 99%